Bis[di(4-methoxyphenyl)amino]carbazole-capped indacenodithiophenes as hole transport materials for highly efficient perovskite solar cells: the pronounced positioning effect of a donor group on the cell performance. Issue 17 (9th April 2019) - Hua, Yong; Chen, Song; Zhang, Dongyang; Xu, Peng; Sun, Anxin; Ou, Yangmei; Wu, Tai; Sun, Hanwen; Cui, Bo; Zhu, Xunjin
Abstract : Two indacenodithiophene-based HTMs have been designed and applied in PSCs. The PSC device based on YK1 displays a very impressive PCE of 20.13%. Abstract : Bis[di(4-methoxyphenyl)amino]carbazole-capped indacenodithiophenes (IDTs) have been constructed as hole transport materials (HTMs) for perovskite solar cells (PSCs). Two IDT-based HTMs, one with 3, 6-bis[di(4-methoxyphenyl)amino]carbazole (YK1 ) and another with 2, 7-bis[di(4-methoxyphenyl)amino]carbazole (YK2 ), show different performances in PSCs. The PSC device based onYK1 displays a very impressive PCE of 20.13% under AM1.5G solar illumination, which is much higher than those of the devices based onYK2 (17.35%) andSpiro-OMeTAD (19.01%) under the same working conditions. This is mainly becauseYK1 has more effective intermolecular π–π stacking, a lower-lying HOMO level and higher hole-mobility thanYK2 andSpiro-OMeTAD . Furthermore, theYK1 -based PSC exhibits excellent long-term stability retaining 94% of the initial PCE value after a 600 h lifetime without encapsulation owing to its better film morphology and hydrophobicity. These findings would shed light on the crucial importance of molecular engineering and allow its extension into general principles for the design of new HTMs for highly efficient and stable PSCs.